Participatory opportunity and constraint analysis and methodology in the conduct of field-scale and community-level case studies for the AgWater Solutions project - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The objective of the project was to identify investment options and opportunities in agricultural water management with the greatest potential to improve incomes and food security for poor farmers. Participatory opportunity and constraint analysis and methodology was used in the field-scale and community-level case studies to understand the complex interaction among social, economic and physical factors that influence the uptake and success of AWM options, and to identify technologies appropriate to different contexts in each of the project countries.